1989
DOI: 10.1029/jd094id14p16665
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of nitric oxide and total reactive nitrogen in the Antarctic stratosphere: Observations and chemical implications

Abstract: Measurements of nitric oxide, NO, and the sum of reactive nitrogen species, NOy, were made as part of the Airborne Antarctic Ozone Experiment (AAOE) on flights of the NASA ER‐2 aircraft over the Antarctic continent. Reactive nitrogen species include NO, NO2, NO3, N2O5, HNO3, and ClONO2. The technique utilized the conversion of NOy components to NO on a gold catalyst and the subsequent detection of NO by the chemiluminescent reaction of NO with O3. NO was measured on two of the flights by removing the catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(52 citation statements)
references
References 52 publications
7
45
0
Order By: Relevance
“…The MLS instrument does not detect HNO, or H,O in condensed phase, but the significant decrease observed in gas-phase HNO, without a corresponding decrease observed in gas-phase H 2 0 is a necessary (albeit not sufficient) condition for the decoupling of these processes.PSCs over most of the Antarctic continent, and gas-phase HNO, values are extremely low ( 1 2 ppbv) throughout this region. A "collar" of high HNO, (r 10 ppbv) is seen just outside the low-temperature region, consistent with previous aircraft observations(23,26) and colocated CLAES measurements(16). The outer boundary of enhanced C10 roughly corresponds to the insist, with mixing ra'tio values less than 6 ppbv and less t h m 3 ppmv, respectively, throughout most of the vortex.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The MLS instrument does not detect HNO, or H,O in condensed phase, but the significant decrease observed in gas-phase HNO, without a corresponding decrease observed in gas-phase H 2 0 is a necessary (albeit not sufficient) condition for the decoupling of these processes.PSCs over most of the Antarctic continent, and gas-phase HNO, values are extremely low ( 1 2 ppbv) throughout this region. A "collar" of high HNO, (r 10 ppbv) is seen just outside the low-temperature region, consistent with previous aircraft observations(23,26) and colocated CLAES measurements(16). The outer boundary of enhanced C10 roughly corresponds to the insist, with mixing ra'tio values less than 6 ppbv and less t h m 3 ppmv, respectively, throughout most of the vortex.…”
supporting
confidence: 81%
“…Because temperatures remain above the frost point at this time, a comparable decrease in H 2 0 vapor is not expected and indeed is not present in the MLS data. Although in situ observations of correlated low concentrations of water vapor and total reactive nitrogen over Antarctica (23) have been taken to imply that the processes of denitrification and dehydration are coupled, other observations (24) have been interpreted to suggest that denitrification can occur without significant dehydration. Theoretical studies (7, 2.5) have found that the sedimentation rate of HNO, particles can be sufficiently rapid-given low cooling rates or cooling to just below the NAT condensation point-for substantial HNO, loss to take place over short time scales, independent of the formation of water ice clouds.…”
Section: Sciencementioning
confidence: 96%
“…Uptake of NO x (NO and NO 2 ) onto MSPs may also have an influence on the atmospheric nitrogen balance, which is dominated by NO in the mesosphere and NO 2 in the stratosphere (Fahey et al, 1989). The coating of MSP surfaces with any of these species, as well as H 2 O, may also alter the chemical reactivity of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Measured reductions in HNO 3 (Coffey et al, 1989;Fahey et aL, 1989b;Gandrud et al, 1989;Toon et al, 1989a) and H20 (Fahey et al, 1989b concentrations inside the antarctic polar vortex compared to those outside point directly to denitrification and dehydration, respectively. Furthermore, the conditions under which PSCs occur over Antarctica suggest that the amounts of HNO 3 and H20 fall from 5-7 ppbv and 4-5 ppmv, respectively, in June to 1-2 ppbv and 2 ppmv in October (see, for example, Watterson and Tuck, 1989).…”
Section: Introductionmentioning
confidence: 99%